Nanotechnology safety - Asmatulu, Ramazan (Elsevier Science & Technology, 2013)
Nanotechnology is a new and emerging discipline that is multidisciplinary and interdisciplinary. The usage of nanosystems, nanomaterials, nano-devices, etc. permeates all aspects of society. Cancer targeting and curing nanosystems are being introduced into the biomedical and pharmaceutical industries; so are lightweight energy absorbing or blast-proof nanohybrid material in the aerospace, automotive and marine industries and high-efficiency energy harvesting nanomaterials, etc. Society has a vested interest in knowing how these new materials, devices and systems are changing the economy and.